The Ark: a customizable web-based data management tool for health and medical research - Bickerstaffe, A.; Ranaweera, T.; Endersby, T.; Ellis, C.; Maddumarachchi, S.; Gooden, G.; White, P.; Moses, Eric; Hewitt, A.; Hopper, J. (Oxford University Press, 2017)
Summary: The Ark is an open-source web-based tool that allows researchers to manage health and medical research data for humans and animals without specialized database skills or programming expertise. The system provides data management for core research information including demographic, phenotype, biospecimen and pedigree data, in addition to supporting typical investigator requirements such as tracking participant consent and correspondence, whilst also being able to generate custom data exports and reports. The Ark is 'study generic' by design and highly configurable via its web interface, allowing researchers to tailor the system to the specific data management requirements of their study. Availability and Implementation: Source code for The Ark can be obtained freely from the website https://github.com/The-Ark-Informatics/ark/ . The source code can be modified and redistributed under the terms of the GNU GPL v3 license. Documentation and a pre-configured virtual appliance can be found at the website http://sphinx.org.au/the-ark/ . Contact: adrianb@unimelb.edu.au. Supplementary information: Supplementary data are available at Bioinformatics online.